Chieftains into Ancestors : Imperial Expansion and Indigenous Society in Southwest China - Ts'ui-p'ing, Ho; Faure, David (Book collections on Project MUSE., 2013)
While official Chinese history has always been written from acentrist viewpoint, Chieftains into Ancestors describes theintersection of imperial administration and chieftain-dominated localculture in the culturally diverse southwestern region of China. Contemplating the rhetorical question of how one can begin to rewritethe story of a conquered people whose past was never transcribed in thefirst place, the authors combine anthropological fieldwork withhistorical textual analysis to build a new regionalhistory one that recognizes the ethnic, religious, andgendered transformations that took place in Chinasnation-building process.